Evaluasi Formulasi Sediaan Sampo Antifungi dari Ekstrak Etanol Bawang Merah (Allium cepa L.) - Megawati Butar-butar (Herbal Medicine Journal, 2023)
Shallot extract (Allium cepa L.) has 29% flavonoids which have potential as antioxidants. The aim of the study was to determine the optimal shampoo formulation from shallot extract which can be applied as an anti-dandruff shampoo. The research method was experimentally by evaluating homogeneity, pH, viscosity, disintegrating power, wetting power, cleaning power, preparation stability, and irritation. The results showed that the shallot ethanol extract shampoo met the quality evaluation requirements.